2019
DOI: 10.1051/e3sconf/201911002102
|View full text |Cite
|
Sign up to set email alerts
|

Use of renewable energy and tax burden on CO2 emissions in industrial enterprises

Abstract: The paper demonstrates the results of studies assessing the specific share of renewable energy facilities in the energy balance of the Russian Federation, analyzes investment in renewable energy throughout the world, as well as in the mining industry. In addition, there is a developed scheme with options for changes in the system of state control in the field of CO2 emissions: 3 options for implementing a system of tax burden on CO2 emissions for industrial enterprises are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In connection with the acceleration of the processes of changes in the modern economy, the necessity and very existence of the "freezing" stage in the life cycle of changes is questioned by a number of researchers. However, other researchers distinguish a certain period necessary for the awareness and acceptance of the new situation that has developed as a result of changes, both at the level of the organization [12][13][14] and at the level of the socioeconomic system as a whole. We consider it expedient to single out the stage of "freezing" in the life cycle of changes, which is necessary for analyzing the results and feasibility of changes, for accepting the object of changes in its results, as well as for reflection on the implementation of projects of changes, but not as the end of the transformation process, but as elements of monitoring with the purpose of identifying and adjusting further projects and change processes according to the spiral development model.…”
Section: Resultsmentioning
confidence: 99%
“…In connection with the acceleration of the processes of changes in the modern economy, the necessity and very existence of the "freezing" stage in the life cycle of changes is questioned by a number of researchers. However, other researchers distinguish a certain period necessary for the awareness and acceptance of the new situation that has developed as a result of changes, both at the level of the organization [12][13][14] and at the level of the socioeconomic system as a whole. We consider it expedient to single out the stage of "freezing" in the life cycle of changes, which is necessary for analyzing the results and feasibility of changes, for accepting the object of changes in its results, as well as for reflection on the implementation of projects of changes, but not as the end of the transformation process, but as elements of monitoring with the purpose of identifying and adjusting further projects and change processes according to the spiral development model.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the study of the problem of green building as a target in managing the quality of construction products must be carried out from the point of view of a value-based approach both for the consumer and for other stakeholders in construction. Based on the conclusions described in the works [6][7][8][9][10], it can be concluded that the implementation of the principles of green building, improvement of the quality parameters of construction facilities, and the introduction of innovations are associated with increased costs. Therefore, taking into account the insufficiently high level of effective demand in Russia and the high degree of competition with conventional construction projects, the requirement for adequate economic profitability of the final and intermediate products of green building is revealed.…”
Section: Methodsmentioning
confidence: 99%